105k views
4 votes

- 6 (1)/(2 ) + 5can I get help

User Nshy
by
4.3k points

1 Answer

4 votes

-6(1)/(2)+5=-(3)/(2)

Step-by-step explanation


-6(1)/(2)+5

Step 1

remember how to convert mixed numbers into fractions


a(b)/(c)=((a\cdot c)+b)/(c)

then, convert the mixed number in the expression


-6(1)/(2)=-((6\cdot2+1)/(2))=-(13)/(2)

Step 2

when you add 2 fractions numbers:


(a)/(b)\cdot(c)/(d)=((a\cdot d)+(b\cdot c))/(b\cdot d)

then,Add the numbers


\begin{gathered} -6(1)/(2)+5 \\ -(13)/(2)+(5)/(1)=(-13\cdot1+2\cdot5)/(2\cdot1)=(-13+10)/(2)=-(3)/(2) \\ \\ -6(1)/(2)+5=-(3)/(2) \end{gathered}

I hope this helps you.

User Gyzerok
by
4.6k points